Struktur Komunitas Plankton Perairan Payau di Kecamatan Wedung Kabupaten Demak - Zakiyyah, Isyarotuz; Hidayat, Jafron Wasiq; Muhammad, Fuad (Bioma : Berkala Ilmiah Biologi, 2016)
Aquaculture are highly prioritized by the government to support the economy. Products from the aquaculture sector is also targeted as a source of income to the Indonesian country. Aquaculture needs to improve to manage water quality, especially plankton to support natural food of the fish. This study aims to examines structure of plankton community in the brackish waters of the District Wedung and then examines the water quality with environmental quality standards of water the cultivation. Research was conducted in February-April 2015. The method used to analyze data that plankton with uses keanekargaman index (H ') and the perataan index ( e ). The results showed that the number of species (genera) plankton obtained during research in the waters of the District Wedung was 45 species, these types consist of 37 species of phytoplankton and zooplankton 8 types. The most common plankton species found in all the stations were Fragillaria sp, Synedra ulna, Oscillatoria formosa and Copepod nauplius. Index of species diversity that existed at the District Wedung moderate to high waters with a range from 1.69 to 2.91 therefore a complex community and stability of the ecosystem were moderate to high. The evennes index ranged from 0.63 to 0.85. Water quality based on the pH, salinity, Turbidity, N, P and organic materials are less good for the cultivation so that the necessary processing on the pond so that according to the criteria of the quality standards of water quality. Keywords: structure of plankton communities, brackish waters, District Wedung